Photovoltaic array maximum power point tracking via modified perturbation and observation algorithm - Bahaa Abdulkhaliq Numan; Amina Mahmoud Shakir; Anas Lateef Mahmood (Institute of Advanced Engineering and Science, 2020)
One drawback of PVs is their low efficiency. As the PVs have a unique maximum Power Point for a specified irradiation level, there must be an effective method for extracting maximum power from the PV module to raise the efficiency. Conventional Perturbation and Observation (P&O) is a simple algorithm for maximum power point tracking (MPPT) but it suffers from oscillation during steady state conditions and is deviated from the maximum power point during slow and rapid irradiation level change. This paper presents a modified P&O by adding variation in PV current as a third in addition to the voltage and power variation parameters. This new algorithm is capable of eliminating the MPPT deviation. To increase the perturbation speed, a double step is taken as the tracking is deviated from the MPP. The modified P&O algorithm is used to control the duty cycle of DC-DC buck converter. The simulation shows that the modified P&O is faster than the conventional. The power loss due to oscillation before attaining the steady state is less for modified P&O. For slow irradiation level change (ramp up 600 to 1000 and ramp down 1000-800) W/m2, the modified P&O shows less tracking diverge. As the irradiation level changes rapidly from 800 to 200 W/m2, it's shown that the modified algorithm attains the steady state faster than the conventional P&O and the average efficiency increased by 4.34%.